2011
DOI: 10.1002/jor.22050
|View full text |Cite
|
Sign up to set email alerts
|

Flavokawain B, a kava chalcone, induces apoptosis in synovial sarcoma cell lines

Abstract: Synovial sarcomas (SS) are soft tissue sarcomas with poor prognosis, displaying a lack of response to conventional cytotoxic chemotherapy. Although SS cell lines have moderate chemosensitivity to isofamide and doxorubicin therapy, the clinical prognosis is still poor. In this article, we showed that flavokawain B (FKB), a novel chalcone from kava extract, potently inhibits the growth of SS cell lines SYO-I and HS-SY-II through induction of apoptosis. Treatment with FKB increased caspase 8, 9, and 3/7 activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 17 publications
3
33
0
2
Order By: Relevance
“…In addition, survivin has demonstrated the ability to prevent the release of apoptosis-induced factor from the mitochondrial intermembrane space, protecting cells against apoptotic death (19,21,22). Futhermore, survivin also suppresses apoptosis via inhibition of the pathway of death receptors and downstream tumor necrosis factor-related apoptosis-inducing ligand (13,18,23,24). The present study was limited to examination of the total apoptosis profile and the protein expression levels of procaspase-3, a principle 'executor', committing cells to death via the intrinsic apoptosis pathway (19,25).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, survivin has demonstrated the ability to prevent the release of apoptosis-induced factor from the mitochondrial intermembrane space, protecting cells against apoptotic death (19,21,22). Futhermore, survivin also suppresses apoptosis via inhibition of the pathway of death receptors and downstream tumor necrosis factor-related apoptosis-inducing ligand (13,18,23,24). The present study was limited to examination of the total apoptosis profile and the protein expression levels of procaspase-3, a principle 'executor', committing cells to death via the intrinsic apoptosis pathway (19,25).…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that licochalcone A suppressed the growth of all the three tested bladder cancer cell lines in a dose-dependent manner (Figure 1). ERK 1/2 has been reported to be involved in drug resistance [11][12][13][14][15][16][17]. …”
Section: Effect Of Licochalcone a On Bladder Cancer Cell Growth And Ementioning
confidence: 99%
“…They exhibit anti-inflammatory [9], anti-invasive [10], anti-tumour [11] and antibacterial [12] properties. Chalcone treatment causes induction of apoptosis and alters mitochondrial membrane potential in various types of cancers [13]. Licochalcone A (LA), an oxygenated chalcone was isolated from the roots of the Chinese liquorice (Glycyrrhiza uralensis).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro kísérletek azt mutatták, hogy a fl awokawain B (új chalcone a kavakivonatból) potenciálisan gátolja az SS-sejtvonalat és apoptózist indukál [45]. Az epigallocatechin-3-gallate hatékony sejtnövekedést gátló szer SSsejtvonalakon [46].…”
Section: Kísérleti Szerekunclassified